2004
DOI: 10.1016/j.tics.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive foundations of cultural stability and diversity

Abstract: The existence and diversity of human cultures are made possible by our species-specific cognitive capacities. But how? Do cultures emerge and diverge as a result of the deployment, over generations and in different populations, of general abilities to learn, imitate and communicate? What role if any do domain-specific evolved cognitive abilities play in the emergence and evolution of cultures? These questions have been approached from different vantage points in different disciplines. Here we present a view th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
269
0
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 457 publications
(303 citation statements)
references
References 64 publications
0
269
0
18
Order By: Relevance
“…Evolutionary psychology (e.g., Barkow et al 1992) also provides a rich theoretical and empirical body of research on biologically evolved features of human cognition that might be predicted to bias cultural transmission in particular directions. Sperber and Hirschfeld (2004) similarly argue that the diversity of some cultural traits, such as religious beliefs or classifications of animals and plants, is the result of adaptation to biologically evolved domain-specific cognitive capacities (e.g., folk biology; Atran 1998). There is also evidence that biomechanical properties of the human vocal apparatus significantly constrain the form of words (MacNeilage & Davis 2000).…”
Section: Evolutionary Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary psychology (e.g., Barkow et al 1992) also provides a rich theoretical and empirical body of research on biologically evolved features of human cognition that might be predicted to bias cultural transmission in particular directions. Sperber and Hirschfeld (2004) similarly argue that the diversity of some cultural traits, such as religious beliefs or classifications of animals and plants, is the result of adaptation to biologically evolved domain-specific cognitive capacities (e.g., folk biology; Atran 1998). There is also evidence that biomechanical properties of the human vocal apparatus significantly constrain the form of words (MacNeilage & Davis 2000).…”
Section: Evolutionary Ecologymentioning
confidence: 99%
“…Hence, although the Fodorian and evo-devo modularity literatures have generally developed separately (but see, e.g., Sperber 2002), Fodorian cognitive modules may be modular in the evo-devo sense. Cognitive structure and processes are essential in supporting and moulding culture Sperber & Hirschfeld 2004). Now, the question is: are the cognitive processes that support cultural evolution modular, do cultural traits themselves form modules, and does this influence cultural evolution?…”
Section: Dwight W Readmentioning
confidence: 99%
“…Sperber 1996, Sperber &Hirschfeld 2004, Sperber andClaidière forthcoming) that psychological mechanisms involved in social learning always involves a combination of preservative and constructive processes. All learning (with the possible exception of rote learning of nonsense 6 material) is biased by content.…”
Section: Preservation and Construction In Cultural Transmissionmentioning
confidence: 99%
“…This is not to say that specific afterlife beliefs -the culturally variable vicissitudes of the hereafter -are direct products of natural selection. As will soon be discussed, investigators such as Boyer (2001) and Atran (2002) have shown that the "selection" of explicit religious ideas occurs at the cultural level, with the "survival" of such ideas being a feature of their ability to become ensconced in the evolved architecture of exposed human minds (Sperber & Hirschfeld 2004). Instead, it is to argue that the subtle contours of a uniquely human adapted design may stand out when closely examining the folk psychology of souls, an intuitive pattern of reasoning that does not appear to hinge on the presence of explicit religious concepts per se (Bering 2002a).…”
Section: By-product Versus Functional Analyses Of Belief In Immortalmentioning
confidence: 99%
“…Instead, many scholars categorize afterlife concepts in the same way they do other types of religious concepts, as especially virulent strains of culturally transmitted ideas that are highly effective at pirating core cognitive architecture (Atran 2002;Boyer 2001; for an exception, see Baron-Cohen 1999). According to this perspective, only the cognitive architecture itself can be the product of natural selection; religious ideas are seen as simply being parasitic on this evolved architecture -as nothing more than noise that shares a general frequency between cultures (e.g., Pyysiäinen 2001;Sperber & Hirschfeld 2004). For example, in his book Religion Explained, Boyer (2001, p. 40) writes: "People have religious notions and beliefs because they acquired them from other people.…”
Section: By-product Versus Functional Analyses Of Belief In Immortalmentioning
confidence: 99%